ADAPTASI DESAIN SIRKULASI GANG KAMPUNG SEKAYU SEMARANG SEBAGAI RUANG PUBLIK RESPONSIF PANDEMI COVID-19 - Krishartadi, Paskalis Noventus; Ristianti, Novia Sari (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Public spaces need to adapt to the COVID-19 pandemic by supporting the implementation of health protocols, so they do not become places for the virus to spread, one of which is the implementation of physical distancing. Alleys in urban kampung as public spaces are undoubtedly prone to spread the virus. The narrow width of the alley makes it difficult for people to implement physical distancing like the alley in Sekayu Kampong in Semarang, which has not shown any adaptation, especially the adaptation of circulation design to support the implementation of physical distancing. The research aims to find and recognize the need for a design for circulation alleys in Sekayu Kampong as a public space responsive to the COVID-19 pandemic. This research approach is quantitative. There are two stages of analysisâ€”first, the user typology analysis in Sekayu Kampong through the behavior and place setting methods. The result is user characteristics: gathering at alley intersections, gathering in alleyways and mobilizing on alleyways. Second, analysis of the needs of circulation design elements with quantitative descriptive methods. Two aspects result. Aspects of the circulation path resulted in a design requirement to utilize another alleyway as an alternative route. Aspects of the direction of circulation resulted in design requirements in circulation signposts and the application of a two-way system that is used alternately, which is applied on Sekayu alley.Abstrak: Ruang publik perlu beradaptasi terhadap pandemi COVID-19 dalam mendukung penerapan protokol kesehatan agar tidak menjadi tempat penyebaran virus, salah satunya penerapan physical distancing. Gang di kampung Kota sebagai ruang publik tentu rawan menjadi tempat penyebaran virus. Ukuran lebar gang yang sempit cenderung membuat masyarakat sulit menerapkan physical distancing. Seperti halnya gang di Kampung Sekayu, Kota Semarang yang belum menunjukkan adanya adaptasi, khususnya adaptasi desain sirkulasi untuk mendukung penerapan physical distancing. Tujuan penelitian ini adalah menemukan dan mengenali kebutuhan desain sirkulasi gang di Kampung Sekayu sebagai ruang publik yang responsif terhadap pandemi COVID-19. Â Pendekatan penelitian ini adalah kuantitatif. Terdapat dua tahap analisis. Pertama, analisis karakteristik pengguna gang di Kampung Sekayu dengan metode behaviour dan place setting. Hasilnya adalah karakteristik pengguna yaitu berkumpul di persimpangan gang, berkumpul di badan jalan gang dan mobilisasi di badan jalan gang. Kedua, analisis kebutuhan elemen desain sirkulasi dengan metode deskriptif kuantitatif. Terdapat dua aspek yang dihasilkan. Aspek jalur sirkulasi dihasilkan kebutuhan desain berupa bentuk pemanfaatan jalur gang lain sebagai jalur alternatif. Aspek arah sirkulasi dihasilkan kebutuhan desain berupa penggunaan papan penunjuk arah sirkulasi dan penerapan sistem dua arah secara bergantian yang diberlakukan di Jalan Sekayu Masjid.